The Hypopi (Acarina: Sarcoptiformes: Hypoderidae) from the Subcutaneous Tissues of Birds in Louisiana. Issue 5 (11th September 2014) - Pence, Danny B.
Abstract : Hypopial nymphs of mites of the family Hypoderidae were recovered from the subcutaneous tissues of 10 species of birds in Louisiana. New host records are established for Hypodectes (Hypodectoides) propus bubulci from Leucophoyx thula and Dichromonassa rufescens and Hypodectes (Hypodectes) nycticoracis from Ixobrychus exilis and Florida caerulea. Additional host records for the above are the former species from Ardea herodius herodius, Bubulcus ibis, and Florida caerulea and the latter from Nycticorax nycticorax. Also, Neottialges (Pelecanectes) eudocimae and Phalacrodectes whartoni from Eudocimus albus, Neottialges (Petecanectes) evansi from Phalacrocorax auritus, and Toucanectes dryocopi from Dryocopus pileatus were collected. Hypodectes (Hypodectoides) propus similimus Ĉerný, 1969 is considered to be a synonym of H. (H.) propus bubulci Fain, 1967 and Alcedinectes alcyon is proposed as a new combination for Gabucinia alcyon Boyd, 1967. The affinities of these species, host-parasite relationships, and certain aspects of the biology of these mites are discussed.